2022
DOI: 10.1093/cercor/bhac507
|View full text |Cite
|
Sign up to set email alerts
|

Associations among body mass index, working memory performance, gray matter volume, and brain activation in healthy children

Abstract: To investigate the neural mechanisms underlying the association between poorer working memory performance and higher body mass index (BMI) in children. We employed structural-(sMRI) and functional magnetic resonance imaging (fMRI) with a 2-back working memory task to examine brain abnormalities and their associations with BMI and working memory performance in 232 children with overweight/obesity (OW/OB) and 244 normal weight children (NW) from the Adolescent Brain Cognitive Development dataset. OW/OB had lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…These findings are in line with other reports of greater NAcc volume with greater adiposity in adolescents [19,20], as well as with longitudinal studies of 9-to 11-year-old children showing that cellular density in the NAcc predicts increases in waist circumference [21] and mediates the relationship between dietary fat consumption and waist circumference [22]. Together, these phenomena [23,24], as well as with reduced volumes in medial OFC and medial superior frontal gyrus [25] and lower volume, cortical thickness, and surface area in middle frontal gyrus [26,27] and dorsolateral PFC [26], whereas analyses of non-US pediatric cohorts have also reported weightassociated reductions in frontal lobe volume [28,29]. Genetic variation at the FTO locus has also been linked with altered structure and function within NAcc and the frontal cortex in…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with other reports of greater NAcc volume with greater adiposity in adolescents [19,20], as well as with longitudinal studies of 9-to 11-year-old children showing that cellular density in the NAcc predicts increases in waist circumference [21] and mediates the relationship between dietary fat consumption and waist circumference [22]. Together, these phenomena [23,24], as well as with reduced volumes in medial OFC and medial superior frontal gyrus [25] and lower volume, cortical thickness, and surface area in middle frontal gyrus [26,27] and dorsolateral PFC [26], whereas analyses of non-US pediatric cohorts have also reported weightassociated reductions in frontal lobe volume [28,29]. Genetic variation at the FTO locus has also been linked with altered structure and function within NAcc and the frontal cortex in…”
Section: Introductionsupporting
confidence: 91%
“…Human imaging studies have been perhaps most concordant in reporting volume reductions in frontal cortex with higher BMI. Cross‐sectional analyses of data in 9‐ to 12‐year‐old children from the large US Adolescent Brain Cognitive Development (ABCD) cohort have demonstrated that greater BMI z score (BMIz) is associated with lower cortical thickness across the prefrontal cortex (PFC) [23, 24], as well as with reduced volumes in medial OFC and medial superior frontal gyrus [25] and lower volume, cortical thickness, and surface area in middle frontal gyrus [26, 27] and dorsolateral PFC [26], whereas analyses of non‐US pediatric cohorts have also reported weight‐associated reductions in frontal lobe volume [28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this context, one highly prevalent exposure that negatively alters brain health is obesity, as it has been associated with detectable structural brain abnormalities underlying executive function. 3,4 Executive function constitutes supervisory control of higher cognitive processes that enable forethought and goal-directed actions. 5 Specifically, executive function refers to specific cognitive domains including working memory (i.e., ability to briefly store and manipulate information), inhibitory control (i.e., ability to suppress irrelevant information and maintain focus), and cognitive flexibility (i.e., ability to shift attention when appropriate) that are vital to success in school and in life.…”
Section: Introductionmentioning
confidence: 99%
“…15 Studies have shown that these physiological confounds may lead to BOLD signal fluctuations that can be mistaken for neuronally driven changes. [16][17][18] Moreover, BMI has been reported to impact task-induced brain activity 19 and resting-state functional connectivity (rs-FC) of both the DMN and ECN. 20 BEN is calculated using the sample entropy (SampEn), which enables estimation of the randomness of the brain activity at rest based on how often different patterns of brain activity are found in the BOLD signal time-series.…”
mentioning
confidence: 99%
“…Blood oxygen level dependent (BOLD) signal as measured by fMRI is a combination of cerebral blood flow, cerebral blood volume, and oxygen consumption rate which are affected by RR, HR, BP, and BMI 15 . Studies have shown that these physiological confounds may lead to BOLD signal fluctuations that can be mistaken for neuronally driven changes 16–18 . Moreover, BMI has been reported to impact task‐induced brain activity 19 and resting‐state functional connectivity (rs‐FC) of both the DMN and ECN 20 …”
mentioning
confidence: 99%